2020
DOI: 10.3389/fmicb.2020.00916
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Eravacycline Resistance in Clinical Enterococcus faecalis Isolates From China

Abstract: Opportunistic infections caused by multidrug-resistant Enterococcus faecalis strains are a significant clinical challenge. Eravacycline (Erava) is a synthetic fluorocycline structurally similar to tigecycline (Tige) that exhibits robust antimicrobial activity against Gram-positive bacteria. This study investigated the in vitro antimicrobial activity and heteroresistance risk of Eravacycline (Erava) in clinical E. faecalis isolates from China along with the mechanism of Erava resistance. A total of 276 non-dupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
(75 reference statements)
1
13
0
Order By: Relevance
“…Given the increasing number of reports of MDR E. faecalis strains, including those resistant to vancomycin and linezolid (Wen et al . 2020); in this study, multidrug resistance was found in 87·5% of E. faecalis . One strain of E. mundtii (Em41) was resistant to linezolid.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…Given the increasing number of reports of MDR E. faecalis strains, including those resistant to vancomycin and linezolid (Wen et al . 2020); in this study, multidrug resistance was found in 87·5% of E. faecalis . One strain of E. mundtii (Em41) was resistant to linezolid.…”
Section: Resultssupporting
confidence: 49%
“…Vancomycin-resistant enterococci were also reported in dust from pig breeding facilities (15%), wild Eurasian necessary to guarantee consistent safety for consumers (Wu et al 2016). Given the increasing number of reports of MDR E. faecalis strains, including those resistant to vancomycin and linezolid (Wen et al 2020); in this study, multidrug resistance was found in 87Á5% of E. faecalis.…”
Section: Antimicrobial Susceptibility Profilementioning
confidence: 67%
“…Remarkably, an important resistance mechanism for tigecycline relies on mutations of ramR and, consequently, RamA-mediated upregulation of the AcrAB-TolC efflux pump [ 38 , 64 , 65 ]. Further efflux-based mechanisms of resistance towards omadacycline and eravacycline have been recently reported [ 66 , 67 , 68 , 69 ]. Moreover, in the case of resistance development against (fluoro)quinolones or β-lactams such as cefoxitin, mutations in ramR were shown to be the primary and most frequent cause for efflux-mediated MDR phenotypes in species such as Salmonella enterica or K. pneumoniae [ 35 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The omadacycline (recently approved for clinical use) and eravacycline (currently in phase 3 clinical trials) derivatives of tetracycline are not subjected to Tet-type RPP-mediated ARE. Though the exact reason for this is unknown, it is likely attributed to the novel moieties at the C9 position of these drugs compared to the parent tetracycline [59,72,73]. The observation that there are several other tetracycline derivatives in phase 1 of the current pharmaceutical pipeline (Table 3) suggests an increased interest in developing this class of AB to target the clinically relevant MDR pathogens.…”
Section: Pharmaceutical Pipeline and Implications For Futurementioning
confidence: 99%